2011
DOI: 10.1590/s0100-204x2011000900012
|View full text |Cite
|
Sign up to set email alerts
|

Identificação e caracterização de genes vip e cry coleóptero‑específicos em isolados de Bacillus thuringiensis

Abstract: O objetivo deste trabalho foi identificar e caracterizar os genes cry3, vip1, vip2 e vip1/vip2 em uma coleção de 1.078 isolados de Bacillus thuringiensis potencialmente tóxicos para larvas de coleópteros. Foram utilizados pares de oligonucleotídeos iniciadores gerais obtidos a partir de regiões conservadas dos genes e do alinhamento de sequências consenso. Posteriormente, os isolados positivos foram caracterizados por meio da técnica de PCR‑RFLP, tendo-se utilizado enzimas de restrição específicas, para identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They are classified into four groups ( http://www.lifesci.sussex.ac.uk/home/Neil_Crickmore/Bt/vip.html ). Vip1 and Vip2 act as a binary protein with activity against coleopteran larvae [3] [4] , Vip3 proteins are active against a large number of economically important lepidopteran pests [5] [6] and, so far, very little is known about Vip4 proteins. Some studies have shown that the transcription of several cry genes in B. thuringiensis occurs before the onset of sporulation [7] and, therefore, at least some Cry and Vip toxins may be expressed together and interact within the insect gut.…”
Section: Introductionmentioning
confidence: 99%
“…They are classified into four groups ( http://www.lifesci.sussex.ac.uk/home/Neil_Crickmore/Bt/vip.html ). Vip1 and Vip2 act as a binary protein with activity against coleopteran larvae [3] [4] , Vip3 proteins are active against a large number of economically important lepidopteran pests [5] [6] and, so far, very little is known about Vip4 proteins. Some studies have shown that the transcription of several cry genes in B. thuringiensis occurs before the onset of sporulation [7] and, therefore, at least some Cry and Vip toxins may be expressed together and interact within the insect gut.…”
Section: Introductionmentioning
confidence: 99%